Motivasi siswa SMP Negeri 13 kota serang dalam mengikuti ekstrakulikuler berbasis sastra di sekolah - Pertiwi, Ismiati; Rizal, Atika Ramadhan; Nabilla, Syifa Aulia; Damayanti, Lely; Wahyuni, Sasa Indri; Aditya, Luthfi (Aksara: Jurnal Bahasa dan Sastra, 2024)
The purpose of this study is to know te various motivation of SMP Negeri 13 Kota Serang students in nonliterary extracurricular activities. This study is a explanatory quantitative research methods. The data collection technique used in this research is form of a questionnaire. This research was taken from students at SMP Negeri 13 Serang using a simple random sampling. The results of the research showed that the competition and competency indicators reached a percentage of 37% with the descriptor "feeling competent in the field of literature" at 9% and the descriptor "having achievements in the field of literature" at 28%. The implication of these findings is that students must be the benchmark where students must improve themselves so that they can participate in literary extracurricular activities at school well and the school must be sensitive to students' motivations whether they are interested or not in participating in literary extracurricular activities at school. Keywords: Extracurricular, SMPN 13 Kota Serang, Student